Techno-Economic and Environmental Assessment of Solar-Powered Electric Vehicle Charging Stations for University Campus under various Planning Horizons - Afzal, Usama (399701); Supervisor: Dr. Syed Ali Abbas Kazmi (Islamabad : USPCAS-E, NUST, 2025)
TH-644
Keywords: MS EEP Thesis; MS Thesis